Understanding the impact of reoccurring and non-financial incentives on plug-in electric vehicle adoption – A review. (January 2019) - Hardman, Scott
Abstract: The market introduction of plug-in electric vehicles (PEVs) is being partially driven by policy interventions. One type of intervention is reoccurring and non-financial incentives, these differ from financial purchase incentives which are a one-time financial incentive associated with the purchase of a PEV. Reoccurring and non-financial incentives include special lane access for PEVs (e.g. HOV/carpool lanes, bus lanes), parking incentives, charging infrastructure development, road toll fee waivers, and licensing incentives. They also include disincentives such as gasoline tax or annual vehicle taxes. The impact of these incentives differs between regions partially due to differences in traffic conditions, travel patterns, consumer preferences, and other local variations. Due to these differences, it is challenging to rank the importance of these incentives, however existing research shows that they all can have a positive impact on PEV adoption. Policymakers wishing to promote the introduction of PEVs will need to consider local travel patterns, the regulatory environment, and consumer preferences to determine the most viable policy interventions for their region.